2017
DOI: 10.3340/jkns.2016.0909.003
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cement-Augmented Percutaneous Screw Fixation for Malignant Spinal Metastases : Is It Feasible?

Abstract: ObjectiveWe evaluated the validity of bone cement-augmented percutaneous screw fixation for treating malignant spinal metastases.MethodsBetween 2011 and 2015, 14 patients (eight men and six women) who underwent bone cement-augmented percutaneous screw fixation for malignant spinal metastases were enrolled in this study. Their life expectancy was considered to be more than one month and less than one year, based on the revised Tokuhashi scoring system. Clinical findings including the back pain scale score, func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Wu et al ( 29 ) implanted CAPS fixation with the assistance of a spinal robot in a patient with multiple spinal metastases of the breast, which effectively improved the patient’s quality of life. Kim ( 30 ) used percutaneous CAPS fixation in 14 patients with spinal metastases. Their results showed that patients’ pain was effectively relieved, which showed that CAPS fixation could provide obvious pain relief and improve the quality of life for some patients with spinal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al ( 29 ) implanted CAPS fixation with the assistance of a spinal robot in a patient with multiple spinal metastases of the breast, which effectively improved the patient’s quality of life. Kim ( 30 ) used percutaneous CAPS fixation in 14 patients with spinal metastases. Their results showed that patients’ pain was effectively relieved, which showed that CAPS fixation could provide obvious pain relief and improve the quality of life for some patients with spinal metastases.…”
Section: Discussionmentioning
confidence: 99%
“… 98 A strategy for the prevention of hardware failure has been proposed by using fenestrated pedicle screw and PMMA augmentation in the vertebral body. 100 102 This augmentation is shown to decrease the risk of screw pull out in both open and minimal access spinal surgery. 100 102 …”
Section: Surgical Managementmentioning
confidence: 99%
“…[100][101][102] This augmentation is shown to decrease the risk of screw pull out in both open and minimal access spinal surgery. [100][101][102]…”
Section: Complicationsmentioning
confidence: 99%
“…Wu et al [25] implanted cement augmented pedicle screw xation with the assistance of a spinal robot in a patient with multiple spinal metastases of the breast, which effectively improved the patient's quality of life. Kim [26] used percutaneous cement augmented pedicle screw xation in 14 patients with spinal metastases. Results showed that the pain of patients was effectively relieved, which showed that cement augmented pedicle screw xation can provide obvious pain relief and improve the quality of life for some patients with spinal metastases.…”
Section: Analysis Of the Curative Effect Of Cement Augmented Pedicle mentioning
confidence: 99%